2005
DOI: 10.1084/jem.20041379
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of antitumor T cells in the blood of melanoma patients before and after vaccination with tumor antigens

Abstract: After vaccination of melanoma patients with MAGE antigens, we observed that even in the few patients showing tumor regression, the frequency of anti-vaccine T cells in the blood was often either undetectable or <10−5 of CD8 T cells. This frequency being arguably too low for these cells to be sole effectors of rejection, we reexamined the contribution of T cells recognizing other tumor antigens. The presence of such antitumor T cells in melanoma patients has been widely reported. To begin assessing their contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(181 citation statements)
references
References 30 publications
(49 reference statements)
10
164
0
6
Order By: Relevance
“…In the course of these studies, we also evaluated the total number of T cells present in the blood that were capable of being stimulated by autologous tumor cells and lysing these tumor cells. Such "anti-tumor" T cells were present in all metastatic melanoma patients at frequencies of ϳ10 Ϫ3 , well above the frequencies of the anti-vaccine T cells (12). Moreover, we observed that these antitumor T cells were already present in the blood of these patients at similar frequencies before vaccination.…”
supporting
confidence: 53%
“…In the course of these studies, we also evaluated the total number of T cells present in the blood that were capable of being stimulated by autologous tumor cells and lysing these tumor cells. Such "anti-tumor" T cells were present in all metastatic melanoma patients at frequencies of ϳ10 Ϫ3 , well above the frequencies of the anti-vaccine T cells (12). Moreover, we observed that these antitumor T cells were already present in the blood of these patients at similar frequencies before vaccination.…”
supporting
confidence: 53%
“…It was shown by Germeau and colleagues that large numbers of antitumor T cells are already present within melanoma patients prior to vaccination with tumor antigens. However, these natural pre-vaccine immune responses are often too weak to result in tumor rejection or even a reduction in tumor growth, due to the various immune suppressive mechanisms that occur within the tumor microenvironment [34]. Vaccination can then aid in boosting these spontaneous immune responses, either by aiding to overcome tumor-induced immune suppression, by re-activating anergic tumorreactive T cells at the tumor site, or by inducing new antitumor CTL clonotypes (probably due to additional antigen release from attacked tumor cells) [3,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies using high-affinity MART-1 TCR-engineered T cells showed severe toxicity, including the destruction of normal melanocytes in the skin, eye, and ear, and sometimes requiring local steroid administration to treat uveitis and hearing loss [203], compared with patient-derived TCR-engineered T cell therapy [206]. Similarly, serious toxicity was not observed with endogenous MAGE-A3-reactive T cells from cancer patients or patients vaccinated with a MAGE-A3 protein [188,207]. MAGE-A3 is highly expressed in cancer cells, but not in normal cells.…”
Section: Tcr-engineered T Cell Immunotherapymentioning
confidence: 93%